Density profile and turbulence evolution during L-H transition studied with the ultra-fast swept reflectometer on ASDEX Upgrade. (10th November 2017) - Medvedeva, A; Bottereau, C; Clairet, F; Hennequin, P; Stroth, U; Birkenmeier, G; Cavedon, M; Conway, G D; Happel, T; Heuraux, S; Molina, D; Silva, A; et al.
Abstract: The ultra-fast swept reflectometer with the sweep time of 1 μ s, inferior to the characteristic turbulent time scale, has provided the measurements of the fast density and density fluctuation evolution across major parts of tokamak plasma radius. The L-H transitions in a series of plasma discharges in ASDEX Upgrade have been studied with a high temporal resolution. The comparison of the density fluctuation behaviour in L- and H-mode is presented. The I-phase oscillation dynamics has been described in terms of the density fluctuation level, the radial electric field and the normalised electron pressure gradient. Indications for a phase shift between the turbulence and the radial electric field are observed in the beginning of the I-phase, where the turbulence grows first and the radial electric field increase follows. In the established I-phase the electric field and the turbulence are in phase.